The Use of Flouting Maxim in â€œRise of the Guardiansâ€ Movie - Ompusunggu, Meysy Claudiana Cindi Agatta; Rudianto, Gaguk (LPPM Universitas Bumigora Mataram, 2023)
This descriptive qualitative research analyzed flouting maxims found in Rise of the Guardians movie. The researchers used utterances that contained flouting maxims as the data and the theory of Grice (1975) was used. Maxims refer to linguistic principles that must be understood in communication between speaker and listener in order for the communication process to proceed well. Flouting maxims refer to the phenomena that happen when communicator do not obey the cooperative principal communication. The phenomena of flouting maxims come up in daily utterance and the existence even appears in movie as media that all utterances are scripted. The aim of this research is to analyze flouting maxims in utterances of Rise of the Guardians movie. In process of collecting data, the researchers used the non-participatory observational method. In this research, pragmatic identity method and the competence in equalizing technique used to analyze the data. Based on the results, the researchers found 10 utterances of flouting maxims from the beginning until end of the movie. Flouting maxim of relation had four utterances, three utterances were found in flouting maxim of manner, one utterance was in flouting maxim of quality, and flouting maxim of quantity appeared two utterances.